APLIKASI MONITORING KEBOCORAN GAS BERBASIS ANDROID DAN INTERNET OF THINGS DENGAN FIREBASE REALTIME SYSTEM - Ardy rimanda putra (Balitbangda Provinsi Lampung, 2020)
Abstract: Supposedly, mineral resources are a very important source in sustaining the Indonesian economy. However, for 74 years Indonesia has managed abundant mineral resources, evenly distributed welfare has not been felt by the community. There is often a rejection of the community against mineral resource management activities. With these facts, of course there are problems in managing mineral resources in Indonesia. One of the problems that will be examined in this study is the sociological aspect of the management of mineral resources in Indonesia. This research uses descriptive qualitative method by collecting data through observation and documentation. After conducting research, it can be concluded that: (1) The mastery of mineral technology in Indonesia is still not optimal, this causes the management of mineral resources in Indonesia is not optimal. (2) Optimization of the management of mineral resources has resulted in state revenues from managing mineral resources to date. (3) Management of mineral resources opens up employment opportunities while increasing the escalation of conflict in the surrounding community. (4) Management of mineral resources has caused environmental damage and caused health problems for the surrounding community. (5) Increasing the economy of the surrounding community as a result of the management of mineral resources in Indonesia is not significant.